The aspect ratio of the palpebral fissure as a new blepharoptosis parameter. Issue 2 (1st April 2022) - Suga, Hirotaka; Takushima, Akihiko
Abstract: Although the margin reflex distance (MRD) is widely used to assess blepharoptosis, it has some drawbacks (e.g. inaccuracy in severe ptosis). A new parameter is desired. We digitally analyzed pre- and post-operative photographs of 95 patients with blepharoptosis. We set a rectangle with the vertical sides at the lateral and medial canthus and the horizontal sides at the highest and lowest points of the eyelids. We calculated the percentage of the vertical side (height) to the horizontal side (width) and defined this value as the vertical percentage of the palpebral fissure. The MRD and the vertical percentage values were strongly correlated (correlation coefficient 0.766). In the 77 bilateral cases, both sides showed significant improvement in vertical percentage (from 28.9 to 37.3%, right) and (28.7 to 36.1%, left). In the 18 unilateral cases, the affected side showed significant improvement in vertical percentage (from 29.6 to 38.7%), while the unaffected side showed no change. In the eight patients who underwent re-operation, the revised side's vertical percentage was not improved after the first operation (from 28.0 to 31.3%), and the revision significantly changed the vertical percentage to 39.0%. In the re-operated patients, the difference between the right and left sides decreased significantly from 6.7 to 1.9% post-revision. The aspect ratio of each palpebral fissure (the percentage of height to width) reflected the progression of blepharoptosis and the post-operative changes. The aspect ratio thus has the potential to be a new parameter for blepharoptosis.